Potential Value of Visfatin, Omentin-1, Nesfatin-1 and Apelin in Renal Cell Carcinoma (RCC): A Systematic Review and Meta-Analysis - Sugania Malar Chinapayan; Shanggar Kuppusamy; Ning Yi Yap; Komathi Perumal; Glenda Gobe; Retnagowri Rajandram (Diagnostics, 2022)
Renal cell carcinoma (RCC) is the most lethal genitourinary malignancy. Obesity is a risk factor for RCC development. The role of adipokines in the relationship between obesity and RCC requires confirmatory evidence in the form of a systematic review and meta-analysis, specifically for visfatin, omentin-1, nesfatin-1 and apelin. A search of databases up to July 2022 (PubMed, Web of Science and Scopus) for studies reporting the association of these selected adipokines with RCC was conducted. A total of 13 studies fulfilled the selection criteria. Only visfatin (p < 0.05) and nesfatin-1 (p < 0.05) had a significant association with RCC. Meanwhile, apelin and omentin-1 showed no association with RCC. The meta-analysis results of nesfatin-1 showed no association with early-stage (OR = 0.09, 95% CI = −0.12–0.29, p = 0.41), late-stage (OR = 0.36, 95% CI = 0.07–1.89, p = 0.23) and low-grade (OR = 1.75, 95% CI = 0.37–8.27, p = 0.48) RCC. However, nesfatin-1 showed an association with a high grade of the disease (OR = 0.29, 95% CI = 0.13–0.61, p = 0.001) and poorer overall survival (OS) (HR = 3.86, 95% CI = 2.18–6.85; p < 0.01). Apelin showed no association with the risk of RCC development (mean difference = 21.15, 95% CI = −23.69–65.99, p = 0.36) and OS (HR = 1.04, 95% Cl = 0.45–2.41; p = 0.92). Although the number of studies evaluated was limited, analysis from this systematic review and meta-analysis indicate that visfatin and nesfatin-1 were elevated. In summary, these adipokines may play a role in the development and progression of RCC and hence may have potential diagnostic and prognostic capabilities for RCC.